Danger and apportunity: Explaining international crisis outcomes - Herring E. (Manchester: Manchester university press, 1995)
The Chinese ideograph for "crisis" is a combination of the characters for "danger" and "opportunity". In this textbook assessment of international crisis behaviour, Eric Herring explains how both are crucial to understanding crisis outcomes. Herring links two analytical perspectives: the view in which the opponent is an aggressor seeking to exploit opportunities; and the view that decision-makers are driven by danger. He examines outcomes in a variety of case studies: classic US-Soviet examples such as the Cuban missile crisis in 1962; clashes between other states, such as the Falklands in 1982; and the major post-Cold War crisis of the Gulf in 1991. Herring argues that nuclear superiority has little effect whereas conventional military superiority - especially locally - can be important in deciding crisis outcomes. However, decision-makers who think they have military superiority tend to misperceive opponents who stand up to them as irrational. Having more at stake than the opponent is a crucial advantage as long as both sides do not want war. Strategic culture affects outcomes indirectly by shaping perceptions of interests, options and opponents.
Inv.: (NP(B/11222s
Keywords: Taiwan -- Berlin -- North -- Korea